2012
DOI: 10.3390/su4050958
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Future Impacts of Environmental Constraints on Human Development

Abstract: Environmental constraints have always had, and will always have, important consequences for human development. They have sometimes contributed to, or even caused, the reversal of such development. The possibility that such constraints, including climate change, will grow significantly this century raises the concern that the very significant advances in human development across most of the world in recent decades will slow or even reverse. We use the International Futures (IFs) integrated forecasting system to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The IFs integrated modeling system (Hughes et al, ) baseline scenario (Hughes et al, ) was used to derive 2015 and 2050 population density, population age structure, and baseline mortality rates for COPD, IHD, CEV, LC, and ALRI. Figure S2 shows the variation in baseline mortality, population age distribution, and population density for India between 2015 and 2050.…”
Section: Methodsmentioning
confidence: 99%
“…The IFs integrated modeling system (Hughes et al, ) baseline scenario (Hughes et al, ) was used to derive 2015 and 2050 population density, population age structure, and baseline mortality rates for COPD, IHD, CEV, LC, and ALRI. Figure S2 shows the variation in baseline mortality, population age distribution, and population density for India between 2015 and 2050.…”
Section: Methodsmentioning
confidence: 99%
“…Future Demographics and Baseline Mortality Rates in IndiaPopulation density, age groupings, and baseline mortality rates are taken from the International Futures (IFs) integrated modeling system(Hughes et al, 2011) baseline scenario(Hughes et al, 2012) for 2015 and 2050. InConibear et al (2018b), we found that the population age distribution in India in 2050 shifts toward older ages relative to 2015 (40 years and older) and there is large population growth, particularly across the Indo-Gangetic Plain.…”
mentioning
confidence: 99%
“…The model has been widely documented and further information can be found through academic sources (Hughes et al., 2009; Hughes, Dickson, & Irfan, 2010; Hughes et al., 2010; Hughes, Irfan, Moyer, Rothman, & Solórzano, ; Moyer & Hughes, ).…”
Section: Methodsmentioning
confidence: 99%